O valor econômico do carbono emitido pelo processo de desmatamento da Amazônia como instrumento de conservação florestal - Lamarca Junior, Mariano Rua (2007)
We analyse in the this work the causes of deforestation of the Legal Amazonia and the environment subject present in the public policies for the region, including the Public Forests Management Law (Law 11.284/06), approved with the goal of regulating public forests management in Brazil and promoting the sustainable development. We discuss the Kyoto Protocol´s Clean Development Mechanism (CDM) problem regarding forest conservation. Through a hypothetical scenario of zero deforestation and 100% of the not emitted carbon linked to forest conservation projects, we calculate that an economic revenue equivalent to the logging activities could be obtained, contributing to the maintenance of the climatic equilibrium because of the reduced Greenhouse Gases emissions, as well as keeping preserved the biodiversity and environment services values related to the standing forest. Nevertheless, appropriate regulations should be planned and implemented to achieve the desired goal, and the solution proposed in this work is in the convergence of the international laws regulating carbon markets and the native tropical forests protection laws